Fetal body organ T2* relaxometry at low field strength (FOREST) - Payette, Kelly; Uus, Alena U.; Aviles Verdera, Jordina; Hall, Megan; Egloff, Alexia; Deprez, Maria; Tomi-Tricot, Raphaël; Hajnal, Joseph V.; Rutherford, Mary A.; Story, Lisa; Hutter, Jana (Medical Image Analysis, 2025)
Fetal Magnetic Resonance Imaging (MRI) at low field strengths is an exciting new field in both clinical and research settings. Clinical low field (0.55T) scanners are beneficial for fetal imaging due to their reduced susceptibility-induced artifacts, increased T2* values, and wider bore (widening access for the increasingly obese pregnant population). However, the lack of standard automated image processing tools such as segmentation and reconstruction hampers wider clinical use. In this study, we present the Fetal body Organ T2* RElaxometry at low field STrength (FOREST) pipeline that analyzes ten major fetal body organs. Dynamic multi-echo multi-gradient sequences were acquired and automatically reoriented to a standard plane, reconstructed into a high-resolution volume using deformable slice-to-volume reconstruction, and then automatically segmented into ten major fetal organs. We extensively validated FOREST using an inter-rater quality analysis. We then present fetal T2* body organ growth curves made from 100 control subjects from a wide gestational age range (17–40 gestational weeks) in order to investigate the relationship of T2* with gestational age. The T2* values for all organs except the stomach and spleen were found to have a relationship with gestational age (p<0.05). FOREST is robust to fetal motion, and can be used for both normal and fetuses with pathologies. Low field fetal MRI can be used to perform advanced MRI analysis, and is a viable option for clinical scanning.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Fetal MRI; Low-field MRI; T2* relaxometry